Gliogenesis but not neurogenesis occurs during the acute phase of vestibular compensation after unilateral vestibular neurectomy - Liang-Wei Chen; Kenneth Lap-Kei Wu; Kin-Wai Tam; Chun-Wai Ma; Yat-Ping Tsui; Chun-Hong Lai; Ying-Shing Chan; Daisy Kwok-Yan Shum (IBRO Neuroscience Reports)
Following unilateral loss of vestibular input, recovery of motor symptoms is achieved within 2 weeks in rodents. Given that neurogenesis was only reported at 1 month post-lesion, whether there is neurogenesis in this early phase of vestibular compensation remains to be investigated. If not, what then is the major cell type that participates in this timeframe? We show abundant nestin-positive cells in the ipsilesional but not contralesional vestibular nucleus (VN) of rats after ablating cell bodies of vestibular nerve at the Scarpa’s ganglion, as confirmed by both magnetic resonance imaging after surgery and histology. Bromodeoxyuridine (BrdU) uptake indicated that these cells actively proliferated. A high proportion of the cells were double-positive for nestin and GFAP as early as 4 days, and up to 2 weeks post-lesion, in contrast to none in control preparations. In contrast, the number of NeuN-positive neural lineage cells in the VN remained constant in both the control and lesioned rats. Furthermore, NeuN-positive cells were not positive for BrdU. However, a small number of proliferating cells stained positive for the immature neuron progenitor marker doublecortin. Taken together, we show that unilateral loss of vestibular input stimulates proliferation of neuroglial progenitors, and provide evidence that argues against occurrence of neurogenesis within the 2 week period in which recovery of postural and motor symptoms occurs.